LONGEVITY OF SOCIO-NATURAL SYSTEMS: TIME-SPATIAL SCALE, INNOVATION AND CITIES - Urushima, Andrea Yuri Flores; Jong, Wil de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2023)
The discussion about the socio-natural systems' future sustainability implies the analysis of the impact of human-environment interactions established from various spatial-time scales on the longevity of systems. Indeed, sustainability and sustainable development related research has shown a methodological and conceptual insufficiency in terms of the analysis of extended spatial and temporal scales. Thus, to contribute to the discussion on the topic, it is worth reassessing the prior notions such as 'milieu' and 'cultural environment' have addressed the formation and maintenance of social-natural systems. A retrospective survey of earlier notions shows that they were based on comprehensive conceptual approaches and suggests relevance of revisiting the role that innovation and urbanisation processes have on the sustainability of socio-natural systems. This paper deals with unexplored analytical, methodological and conceptual issues on the longevity of socio-natural systems.
Keywords: socio-natural systems; spatial-time; scale; innovation; city